Systematic analysis of the BET family in adrenocortical carcinoma: The expression, prognosis, gene regulation network, and regulation targets - Situ, Yongli; Liang, Quanyan; Zeng, Ziying; Chen, Jv; Shao, Zheng; Xu, Qinying; Lu, Xiaoyong; Cui, Yongshi; Zhang, Juying; Lu, Lingling; Deng, Li (Frontiers in Endocrinology, 2023)
Background: Bromodomain and extracellular terminal (BET) family (including BRD2, BRD3, and BRD4) is considered to be a major driver of cancer cell growth and a new target for cancer therapy. However, the expression levels, gene regulatory networks, prognostic value, and target prediction of BRD2, BRD3, and BRD4 in adrenocortical carcinoma (ACC) have not been fully elucidated. Methods: multiple databases were used. Results: The expression levels of BRD3 and BRD4 were significantly upregulated in ACC patients at different cancer stages. Moreover, the expression of BRD4 was significantly correlated with the pathological stage of ACC. ACC patients with low BRD2, BRD3, and BRD4 expressions had longer survival than patients with high BRD2, BRD3, and BRD4 expressions. The expression of BRD2, BRD3, and BRD4 was altered by 5%, 5%, and 12% in 75 ACC patients, respectively. Molecular functions related to BRD2, BRD3, and BRD4 and their neighboring genes mainly include protein-macromolecule adaptor activity, cell adhesion molecule binding, and aromatase activity. Chemokine signaling pathway, thiamine metabolism, and olfactory transduction were found to be enriched as per the KEGG pathway analysis. SP1, NPM1, STAT3, and TP53 are key transcription factors for BRD2, BRD4, and their neighboring genes. MiR-142-3P, miR-484, and miR-519C were the main miRNA targets of BRD2, BRD3, BRD4, and their neighboring genes. We analyzed the mRNA sequencing data from 79 patients with ACC and found that ZSCAN12, DHX16, PRPF4B, EHMT1, CDK5RAP2, POMT1, WIZ, ZNF543, and AKAP8 were the top nine genes whose expression were positively associated with BRD2, BRD3, and BRD4 expression. The expression level of BRD2, BRD3, and BRD4 positively correlated with B cell and dendritic cell infiltration levels. BRD4-targeted drug PFI-1 and (BRD2, BRD3, and BRD4)-targeted drug I-BET-151 may have good inhibitory effects on the SW13 cell line. Conclusions: The findings of this study provide a partial basis for the role of BRD2, BRD3, and BRD4 in the occurrence and development of ACC. In addition, this study also provides new potential therapeutic targets for ACC, which can serve as a reference for future basic and clinical research.